2019
DOI: 10.1088/2057-1976/ab169e
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional (3D) dose distribution measurements of proton beam using a glass plate

Abstract: The measurements of the three-dimensional (3D) dose distribution of proton beams in water are critical for proton therapy for quality assessment (QA). Although ionization chambers are commonly used for this purpose, such measurements take a long time to calculate precise 3D dose distribution.To solve this problem, we measured 3D dose distributions using a glass plate. We placed a 1-mm thick float glass plate on the upper inside of a black box with a water tank set above the float glass plate outside the black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Although the ZnS scintillator yielded smaller LET dependence (quenching effect) than the Gd scintillator for carbon ions, it still required small corrections (maximum of approximately 20%) to obtain the correct 3D dose distributions for carbon ions. Previous studies reported that, for a proton beam with a lower LET, 3D dose distributions showed good agreement with those obtained using a float glass plate that had no quenching effect [ 26 , 27 ]. The float glass provides the advantage of a light output—approximately 20 times higher than that of silica glass, which does not undergo proton quenching [ 28 ].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Although the ZnS scintillator yielded smaller LET dependence (quenching effect) than the Gd scintillator for carbon ions, it still required small corrections (maximum of approximately 20%) to obtain the correct 3D dose distributions for carbon ions. Previous studies reported that, for a proton beam with a lower LET, 3D dose distributions showed good agreement with those obtained using a float glass plate that had no quenching effect [ 26 , 27 ]. The float glass provides the advantage of a light output—approximately 20 times higher than that of silica glass, which does not undergo proton quenching [ 28 ].…”
Section: Discussionsupporting
confidence: 57%
“…The depths indicated the water-equivalent depths (WEDs), which included the bottom wall of the tank (11.6 mm of PMMA) and the black aluminum plate (0.6 mm) above the scintillator. Each 3D image was created from the corresponding measured 2D image using ImageJ [ 26 ]. To compensate the quenching effect (brightness reduction due to a higher LET), correction factors were multiplied to the brightness of the images at each depth.…”
Section: Methodsmentioning
confidence: 99%
“…In proton therapy, validation of dose distribution is vital to verifying the irradiation system can treat patients and deliver the prescribed plan, particularly due to the significant dose deposition at the Bragg peak. There has been an interest in measuring precise three-dimensional (3D) dose profile of proton beams and scintillation and radioluminescence imaging has shown promising methods of acquiring volumetric dose distributions [1][2][3]. Optical imaging inherently provides two-dimensional (2D) dose profiles and require reconstruction methods to produce a 3D dose distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Optical imaging inherently provides two-dimensional (2D) dose profiles and require reconstruction methods to produce a 3D dose distribution. Some methods include multiple acquisitions of 2D radioluminescence slices of the dose profile [1] or imaging the scintillation projection dose profiles from orthogonal views with multiple cameras [3].…”
Section: Introductionmentioning
confidence: 99%
“…One high-resolution and cost-effective method to measure 3D optical images is to stack measured 2D optical images perpendicular to the beam direction. In this method of measuring 3D optical images of radiation, a scintillator plate such as a plastic scintillator [19], float glass [20], or ZnS(Ag) [21] has been used in the imaging to measure the cross sections of beams. The depths of these cross sections were changed by adding water in a container set above the scintillators [19][20][21].…”
Section: Introductionmentioning
confidence: 99%